Intensification Of Arable Agricultural Land Use As A Response To Changing Agro-Ecological Context In The Benue Basin, Nigeria - Ortserga, Daniel S.; Kwaghsende, Felix K.; Dam, Daniel P.; Kile, Tracy I.; Ujoh, Fanan; Gyuse, Timothy T. (Advances in Social Sciences Research Journal, 2019)
This study investigated intensification of rural agricultural land use as a response to the changing agro-ecological context in the Benue basin. The objectives were to describe the changing agro-ecology of the region that is stimulating this response from farmers and to assess the level of agricultural land use intensification in the area. Field survey was the main design for data collection and was supplemented by archival search to access knowledge on the process of state intervention in the agricultural systems, population and settlement change in the area. A sample of 1,500 farming households, shared uniformly among the five states covered by the study, was used and questionnaire was the major instrument for data collection. In addition, the study made field observations and took photographs to depict farm scenes. Results showed that agro-ecological circumstances in the region have altered as manifested in over 100% rise in average population densities since 1991 in all the five states investigated as well as rapid urban expansion. It was also found that access to new farming technologies in form of new crop varieties, fertilisers and other farm chemicals has improved for 78% of respondents in the area through activities of government agencies such as agricultural institutions, agricultural development projects and river basin development authorities, and large scale farms which have emerged in the region. Also significant is the finding that farmers in the basin have accepted the philosophy and principles of productivist agriculture which commoditise production for the market. They are therefore prepared to accept the limited innovations that are available. The study recommends deliberate policy to exploit farmers’ disposition towards innovation adoption and commercialisation of production in the area through improved access to new farm technologies and extension services.